Hubungan Batas Cair dan Plastisitas Indeks Tanah Lempung yang Distabilisasi dengan ISS 2500Terhadap Nilai Kohesi pada Uji Geser Langsung dan Uji Tekan Bebas - Manik, Markus; Iswan, Iswan; Jafri, Muhammad (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
Along with the times, human need a better means and facilities. This make human have no choicebut to build a building or civil structure upon improper area, for example, build it on clay area.The clay is a cohesive soil which often undergoing a swelling-shrinking event in its subgrade. So,it needed to to carried out the stabilization, one of which is using ISS 2500, and research of liquidlimit and plasticity index to know about their relationship with its cohesion in-depth study.Thesample was taken from Margakaya village and Palputih village, District of Jati Agung, SouthLampung and Blimbing Sari village, District of Jabung, East Lampung. The soil tested at originalcondition and mixed by ISS2500 with three variation of mixture, that is at 0,6 ml, 0,9 ml, and 1,2ml. Mixing is conducted based on optimum moisture content of each kind of soil. Mechanicaltesting which is unconfined compressive test and direct shear test, using three sample for everysoil and every mixture variation.Test result show that the more volume of solution added into soil1, soil 2 and soil 3, then it will increase value of soil cohesion (c), maximum stress (qu). Mixing ofthe ISS 2500 resulted liquid limit (LL) of clay be between 42% - 47% .Keywords: cohesion, direct shear test, liquid limit, plasticity index, unconfined compressive test